An inverse radiation model for optical determination of temperature and species concentration: Development and validation. (January 2015) - Ren, Tao; Modest, Michael F.; Fateev, Alexander; Clausen, Sønnik
Abstract: In this study, we present an inverse calculation model based on the Levenberg–Marquardt optimization method to reconstruct temperature and species concentration from measured line-of-sight spectral transmissivity data for homogeneous gaseous media. The high temperature gas property database HITEMP 2010 (Rothman et al. (2010)[1] ), which contains line-by-line (LBL) information for several combustion gas species, such as CO2 and H2 O, was used to predict gas spectral transmissivities. The model was validated by retrieving temperatures and species concentrations from experimental CO2 and H2 O transmissivity measurements. Optimal wavenumber ranges for CO2 and H2 O transmissivity measured across a wide range of temperatures and concentrations were determined according to the performance of inverse calculations. Results indicate that the inverse radiation model shows good feasibility for measurements of temperature and gas concentration. Abstract : Highlights: An inverse radiation model to deduce temperature and concentration is developed. This model is validated by measured transmissivity for CO2 and H2 O. The possible deficiencies in the HITEMP database is discussed. Optimal spectral ranges for inverse calculation are identified.